Pemanfaatan Aplikasi Google Classroom Sebagai Media Pembelajaran Daring - Rai Tirtawati, Anak Agung; Mari Meroho, Imanuel Dara (Dwijendra University, 2022)
The Google Classroom application is one of the free Web-based access that makes it easier for lecturers and students in online learning in the Covid-19 pandemic era. Today's development is inseparable from Information Technology (IT) which is also growing. Information technology is one of the tools managers use to inspire developmental change. This study uses a quantitative approach with research subjects are students of communication science and responds to research questions with data collection techniques using questionnaires to collect research results from respondent students. The conclusion of the research is the data collection technique using a questionnaire that was adopted from the study. The variables of this study consisted of the use of the Google Classroom Application as an online learning media which consisted of 10 question indicators to obtain respondents from the research results. This research uses quantitative and qualitative approach with descriptive analysis